Animals and the World of the Supernatural - Kmecová, Svetlana (Poznańskie Studia Slawistyczne, 2021)
Phraseological stocks of all languages contain numerous phrasemes with zoonym components. In the paper the author deals with Slovak and Slovene zoonym phrasemes which demonstrate ancient ideas of ancestors about interconnections between animals and the world of the supernatural, in relevant cases she also deals with other phenomena related to the subject of the paper. A number of phraseological units reflect the belief that animals used to have the ability to sense upcoming events, predict the weather, misfortune or death. The units listed in the paper are often rather archaic, however, many of them are still in use or the idea they represent is still alive. The analysed language material has shown similarity not only between Slovak and Slovene languages but also between the mental concepts which form the language picture of the world of their users.